Cancer and the entangled creator: Deep incarnation and the analeptic cross. Issue 4 (18th January 2023) - Simmons, Ernest Lee
Abstract: The metaphorical appropriation of quantum entanglement (non‐local relational holism) helps to conceptualize the physical relationship of God to creation in a way which can support the understanding of deep incarnation. The relational holism of Divine entanglement helps clarify how deep incarnation is possible. Deep incarnation in turn assists with the understanding of God's connectivity and ongoing relationality to a suffering world, bringing hope and love in the midst of the pain and loss of evolutionary biology gone awry, including in cancer. The Logos of creation is also a suffering Logos, a Logos Pathos, that makes hope possible at such times and gives rise to what may be referred to as an Analeptic Cross, the cross embracing and "taking up" all of evolutionary suffering from the beginning. The Analeptic Cross is a way of revealing or making manifest the Logos Pathos . The article concludes with the role of faith in grounding hope in the midst of loss, providing resilience and courage in the midst of uncertainty. Deep incarnation means that God is with us even in the midst of malignancy .